Corn vs. sorghum and pellets vs. meal for growing-finishing swine - Koch, B.A. (Kansas Agricultural Experiment Station, 2011)
This is continuation of feeding trials comparing the feeding value of corn and sorghum grain under Kansas conditions. Forty feeder pigs, 12 Poland Chinas and 28 Durocs averaging 55 pounds each, were randomly divided by breed and sex into four groups. All pigs had been previously vaccinated for cholera and erysipelas and wormed with piperazine.
Keywords: Swine; Corn vs. sorghum; Pellets vs. meal; Growing-finishing swine